2022
DOI: 10.1186/s12872-022-02931-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum marker and CT characteristics of coronary calcified nodule assessed by intravascular ultrasound

Abstract: Background Calcified nodule (CN) is a type of potentially vulnerable plaque. Its formation mechanism remains unknown. This study was to assess serum marker and computed tomography angiography (CTA) characteristics of CN validated by intravascular ultrasound (IVUS). Methods Patients who underwent coronary CTA followed by invasive coronary angiography and IVUS were retrospectively analyzed. Serum levels of alkaline phosphatase (ALP), gamma-glutamyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Hence, they proposed ALP as an independent predictor of and biochemical marker for calcification and plaque vulnerability. Similarly, Li et al 52 found an association between calcified nodules, a characteristic of some plaques that have ruptured, and high serum ALP level.…”
Section: Laboratory Testsmentioning
confidence: 87%
“…Hence, they proposed ALP as an independent predictor of and biochemical marker for calcification and plaque vulnerability. Similarly, Li et al 52 found an association between calcified nodules, a characteristic of some plaques that have ruptured, and high serum ALP level.…”
Section: Laboratory Testsmentioning
confidence: 87%